TINJAUAN PELAKSANAAN PEMBUKAAN REKENING TABUNGAN HAJI PADA BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU UIN SYARIF HIDAYATULLAH - Indah Khairunnisa, (2023)
This researcher aims to determine the marketing strategy for haj savings products in retaining Indonesian hajj customers at Bank Syariah Indonesia Sub-Branch Office of UIN Syarif Hidayatullah, to find out the obstacles faced by Bank Syariah Indonesia Sub-Branch Office of UIN Syarif Hidayatullah, and also to find out the challenges that faced in marketing the products of Bank Syariah Indonesia Sub-Branch Office of UIN Syarif Hidayatullah. This qualitative research method uses a descriptive case study-based approach. Data collection is done by using interviews and documents. The data sources used are primary data, namely information that comes from direct observation to Bank Syariah Indonesia KCP UIN Syarif Hidayatullah, interviews with Branch Operations & Service Managers, Back Offices, and Customer Service of Bank Syariah Indonesia KCP UIN Syarif Hidayatullah. Meanwhile, secondary data is obtaining data from literature studies to complement primary data. the results of his research show that Bank Syariah Indonesia is quite good, but there are still deficiencies, namely ATM machines that are not spread in several places.